2011
DOI: 10.1080/1745039x.2010.534897
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of amino acids in organically cultivated white-flowering faba bean and cake from cold-pressed rapeseed, linseed and hemp seed in growing pigs

Abstract: The study aimed at determining the ileal apparent (IAD) and standardised ileal (SID) digestibility of crude protein (CP) and amino acids (AA) in organically cultivated white-flowering faba beans (Vicia faba), and cakes from hemp seed (Cannabis sativa), linseed (Linum usitatissimum) and rapeseed (Brassica napus). The experiment was designed as a four period cross-over trial with six castrated male Yorkshire pigs fitted with post valve T-caecum (PVTC) cannulas. The IAD and SID of CP for the feed ingredients rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
(35 reference statements)
3
8
1
Order By: Relevance
“…In previous studies, Lindberg (1997a, 1997b) reported digestibility values for dietary components and energy in lucerne, white clover, red clover and perennial ryegrass. However, the low inclusion levels applied make values derived by difference calculation very vulnerable even to small errors in the dataset, which has been acknowledged earlier in studies estimating the digestibility of feed ingredients by difference calculation (Høøk Presto et al 2011). The WB and SBP are well studied high-fibre feedstuffs in pig nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Lindberg (1997a, 1997b) reported digestibility values for dietary components and energy in lucerne, white clover, red clover and perennial ryegrass. However, the low inclusion levels applied make values derived by difference calculation very vulnerable even to small errors in the dataset, which has been acknowledged earlier in studies estimating the digestibility of feed ingredients by difference calculation (Høøk Presto et al 2011). The WB and SBP are well studied high-fibre feedstuffs in pig nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…However, digestibility values obtained through difference calculations gets very vulnerable, even to small errors in the dataset, when low inclusion levels are applied. This has also been acknowledged earlier in studies estimating the digestibility of feed ingredients by difference calculation (Høøk Presto et al 2011;Ivarsson et al, 2012). Although inclusion level of SI and SC silage was the same, SC pigs consumed a lower amount of the silage, which might have had a negative effect on the estimation of energy and nutrient digestibility.…”
Section: Discussionmentioning
confidence: 55%
“…[ 58 ]. Additionally, non-GM legume crops, which are locally produced and can be protein alternatives and nutrient-rich sources, are in great demand for the improvement of the self-sufficiency and sustainability of farming systems [ 59 , 60 , 61 , 62 ]. Recent metabolomics studies have focused on the phytochemical/antioxidant properties of different V. faba seed germplasm [ 5 , 63 ] and highlighted the importance of increasing its consumption by humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there are no such studies regarding V. faba seed metabolomics and its impact on supplements for animal feed. The only studies referring to V. faba used for animal feed, are mainly focused on ensiled products and on specific metabolites [ 59 , 64 ], or on its use as a protein alternative to soybean meals [ 60 ].…”
Section: Introductionmentioning
confidence: 99%